Religion, Nonreligion and the Sacred: Art and the Contemporary Rituals of Birth - Anna M. Hennessey (MDPI AG, 2021)
This paper looks at the role of art and material culture in the rituals of birth, first taking into consideration research on material culture in traditional rituals of birth and then turning to the primary topic, which is how art in the contemporary rituals of birth often holds sacred meaning even when the ritual is of a nonreligious nature. A discussion about the sacred in the context of a nonreligious ritual hinges upon an understanding of that which is “sacred”; thus, the paper looks at research on modern theology and the sacred to examine the term in the context of birth as a contemporary rite of passage. Giving examples of how material culture has been important in several traditional birth rituals from different cultures, the paper then traces a similar occurrence in which participants in contemporary nonreligious rituals of birth also uphold art and material culture as sacred elements of the rituals. The paper provides the reader with description of a rich array of art and material culture used across cultures in different rituals of birth. Taking into consideration the numerous contributions that scholars have made to the emerging field of birth and religion, including the interdisciplinary importance of theories related to birth as a rite of passage, the paper also presents new research on the materiality of the contemporary rituals of birth.